Murder in the courthouse : a Hailey Dean mystery - Grace, Nancy, 1959- (2016)
"Hailey Dean is in trouble again-and this time it could be deadly! Hailey Dean, the prosecutor who never lost a case, heads to Savannah as an expert witness on the sensational Julie Love-Adams murder trial, but she soon finds herself embroiled in a mystery. and an unexpected love affair. At the baggage claim, Hailey is greeted by the handsome Lieutenant Chase Billings. On their way to her hotel, they hear an APB for a murder that has just been committed. When they race to the scene, they find Alton Turner, a courthouse sheriff known for being as neat as a pin. Only he's a hot mess now, lying sprawled in a pool of blood, severed in half by a garage door. Hailey, never one to mind her own business, jump-starts Turner's murder investigation while juggling the Julie Love trial. The timing of the trial and murder could be a coincidence, but everyone knows there is no such thing as coincidence in criminal law! Next, Elle Odom, a gorgeous court clerk, is poisoned at the courthouse cafeteria coffee bar. Then, the police tech who helps find Elle's missing handbag (stuffed with her life-saving Epi-pen) turns into alligator bait at an amusement park... and that's just the beginning. With Lt. Billings falling hard for Hailey, she digs deeper to find a killer with a very mysterious agenda. knowing full well the next murder victim may very well be herself. It's crime sleuth Hailey Dean at her best!"--
""Hailey Dean becomes embroiled in a murder investigation and finds herself falling for a handsome lieutenant"--Provided by publisher"--
Recreational Reading Collection
Keywords: Women lawyers -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction; Love stories